Female germline stem cells: recent advances, opportunities, and challenges to overcome - Yaoqi Huang; Haifeng Ye (Cell Regeneration)
Abstract In the field of reproductive medicine, delaying ovarian aging and preserving fertility in cancer patients have long been core issues and relentless pursuits. Female germline stem cells (FGSCs) have been shown to repair aging or damaged ovarian structures and to restore ovarian reproductive and endocrine function. With their unlimited proliferation and directed differentiation into oocytes, FGSCs bring new hope to patients with ovarian insufficiency, malignant tumors, and others needing fertility preservation. In this review, we introduce the role of FGSCs in ovarian fertility preservation and regenerative repair, emphasizing the regulatory pathways of FGSCs in restoring ovarian function. We discuss the unique advantages of FGSCs in infertility treatment, including fertility preservation, animal gene editing, and regenerative medicine. This article aims to offer new research insights for advancing the clinical translation of FGSCs by exploring them from multiple perspectives, such as origin, regulation, and application.